Efectos de la pandemia covid19 en hábitos de sedentarismo y obesidad en niños de edad escolar (2022)
Obesity in school-age children is an increasingly common cause of consultation. This disease, which is considered an epidemic for the world health organization, becomes worrying at the time of relation to the effects of pandemics such as the current COVID -19, the habits that affect children of school age, which are more tempted by marketing and labeling for the constant consumption of foods that do not provide adequate micronutrient intake. The objective is to recognize in school sedentary life how the COVID -19 pandemic generates obesity habits in some school-age children. The work was qualitative, descriptive, having a hermeneutical historical approach, and a sample approached from the documentary review with articles taken in databases Scielo, Dialnet, EBSCO, where there are 16 articles that talk about nutrition, 12 about obesity, 10 for sedentary lifestyle and 4 for anxiety. Results are found that show studies where school age is the lowest rate of nutrients and components that do not contribute to the proper functioning of human metabolism. Where school-age children need a series of healthy and nutritious foods since they have a constant growth stage and based on studies that they must eat between four to five times a day to be able to supply the adequate amount of daily food.